A monitoring and evaluation system for complexity : a case study of the Brazilian national innovation policy - Salles-Filho, Sergio Luiz Monteiro; Carneiro, Ana Maria; Spatti, Ana Carolina; Muraro da Silva, Vinicius; Vonortas, Nicholas; Falcini dos Santos, Gabriel (De Gruyter studies in innovation and entrepreneurship, 2024)
This chapter delves into the evaluation of national innovation policies through a case study of the Brazilian National Innovation Policy (NIP). Assessing these policies poses several challenges, including the difficulty of defining and measuring policy outcomes, the scarcity of reliable data, and the intricacies of interactions among various stakeholders involved in the policy. Additionally, political and economic factors, such as shifts in government leadership and economic fluctuations, can impact the evaluation process. The chapter presents a comprehensive framework for monitoring and evaluating the NIP based on models for continuous policy, program, and institution evaluation. It encompasses a theory of change and a logical framework, along with a set of indicators, benchmarking platforms, and a protocol for implementing the monitoring and evaluation model. This model was developed in collaboration with various stakeholders, including government bodies, academia, and the private sector. The purpose of such a comprehensive framework extends beyond real time knowledge acquisition about policy outcomes, efficacy, and effectiveness. It also aims to address the volatility characterizing innovation-related policies and programs in the country over the past two decades or so.